Superior glucose metabolism supports NH4+ assimilation in wheat to improve ammonium tolerance - Hu, Jinling; Zheng, Qiaomei; Neuhäuser, Benjamin; Dong, Chaofeng; Tian, Zhongwei; Dai, Tingbo (Frontiers in Plant Science, 2024)
The use of slow-release fertilizers and seed-fertilizers cause localized high-ammonium (NH4+) environments in agricultural fields, adversely affecting wheat growth and development and delaying its yield. Thus, it is important to investigate the physiological responses of wheat and its tolerance to NH4+ stress to improve the adaptation of wheat to high NH4+ environments. In this study, the physiological mechanisms of ammonium tolerance in wheat (Triticum aestivum) were investigated in depth by comparative analysis of two cultivars: NH4+-tolerant Xumai25 and NH4+-sensitive Yangmai20. Cultivation under hydroponic conditions with high NH4+ (5 mM NH4+, AN) and nitrate (5 mM NO3-, NN), as control, provided insights into the nuanced responses of both cultivars. Compared to Yangmai20, Xumai25 displayed a comparatively lesser sensitivity to NH4+ stress, as evident by a less pronounced reduction in dry plant biomass and a milder adverse impact on root morphology. Despite similarities in NH4+ efflux and the expression levels of TaAMT1.1 and TaAMT1.2 between the two cultivars, Xumai25 exhibited higher NH4+ influx, while maintaining a lower free NH4+ concentration in the roots. Furthermore, Xumai25 showed a more pronounced increase in the levels of free amino acids, including asparagine, glutamine, and aspartate, suggesting a superior NH4+ assimilation capacity under NH4+ stress compared to Yangmai20. Additionally, the enhanced transcriptional regulation of vacuolar glucose transporter and glucose metabolism under NH4+ stress in Xumai25 contributed to an enhanced carbon skeleton supply, particularly of 2-oxoglutarate and pyruvate. Taken together, our results demonstrate that the NH4+ tolerance of Xumai25 is intricately linked to enhanced glucose metabolism and optimized glucose transport, which contributes to the robust NH4+ assimilation capacity.